The Effect of Online Customer Reviews and Affiliate Marketing on Impulsive Buying of Products in the Shopee Marketplace - Ratih Amelia; Amin Hou; Indra Budiman; Debora Tambunan; Emma Novirsar (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the influence online customer reviews and affiliate marketing against impulsive buying on products in the Shopee marketplace. This type of research is qualitative research, population and sample of this study amounted to 135 people have made purchases of products on Shopee. Data analysis techniques of this study using multiple regression analysis and hypothesis testing. The results of this study show that Online customer reviews have a positive and significant effect on Impulsive Buying on products in the Shopee Marketplace. At 0.799 this means that 79.9% of the variance in the value of impulsive buying on products in Shopee Marketplace is determined or explained by independent variables, namely online customer review and affiliate marketing, while the remaining 20.1% is influenced by other variables that are not studied in this study product promo, product quality and others.